The Orphic ‘fleeting glimpse’ in some of its Remediations - Bär, Gerald (Amaltea. Revista de Mitocrítica, 2025)
The myth of Orpheus and Eurydice was revitalized and perpetuated during the first decades of the twentieth century in literature and other arts. Influenced by literature, painting and music, cinema has retold and re-enacted the myth of Orpheus and Eurydice in many variations, from Fritz Lang’s Destiny (1921) to Jean Cocteau’s Orphic trilogy (1930-60). It is impossible to show the whole process of the myth’s trans-mediation, from orality to internet, but by revisiting the Orphic theme in some of its various modernist re-mediations and by analysing and comparing its pictorial and cinematographic expression we will gain insight not only into its adaptations and transformations, but also into the technology involved in these processes (media archaeology). My approach focuses on the technical reproducibility of the invisible, and analyses its pictorial, poetic and cinematographic expression in the cultural exchange between Rodin, Rilke and Cocteau.
Keywords: Myth; Orpheus; Media archaeology; Painting; Film